2020
DOI: 10.1177/2332858420929978
|View full text |Cite
|
Sign up to set email alerts
|

Stasis and Change in Public School District Racial/Ethnic Segregation, 1993–2015

Abstract: Scholars have often suggested that racial integration is inherently unstable—a transition point in the racial transformation of neighborhoods and schools. While much empirical attention has been paid to documenting changes in segregation in public school districts, in this study we provide initial evidence focusing on the stability of segregation patterns. We calculate annual measures of district racial/ethnic segregation from the National Center for Education Statistics Common Core of Data from 1993 to 2015. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Overall, we observe deteriorating levels of racial integration for Latino children attending elementary schools 2000-2015. Stroub and Richards (2013) reported gains in racial integration for Latino students (on the entropy index for 350 metro areas) in the early twenty-first century, along with stable levels in many parts of the nation (Richards et al 2020). We found modest gains in the odds of interaction between poor and nonpoor elementary students (Fuller et al 2019).…”
Section: Discussion and Policy Implicationsmentioning
confidence: 48%
See 3 more Smart Citations
“…Overall, we observe deteriorating levels of racial integration for Latino children attending elementary schools 2000-2015. Stroub and Richards (2013) reported gains in racial integration for Latino students (on the entropy index for 350 metro areas) in the early twenty-first century, along with stable levels in many parts of the nation (Richards et al 2020). We found modest gains in the odds of interaction between poor and nonpoor elementary students (Fuller et al 2019).…”
Section: Discussion and Policy Implicationsmentioning
confidence: 48%
“…Earlier, Rivkin (1994) found two contradictory trends in the immediate wake of the civil rights era: Black children had become more evenly distributed among schools within districts, yet racial segregation between districts intensified, mostly due to White flight. Later Stroub and Richards (2013) found that evenness within districts between Black and White students improved slightly nationwide from 1998 to 2009, while remaining stable in most parts of the country (Richards et al 2020). But the separation of Black from White peers between districts had continued to worsen (Clotfelter 2001;Logan et al 2008).…”
Section: Segregation Between and Within School Districtsmentioning
confidence: 99%
See 2 more Smart Citations
“…Demographers and sociologists, alternatively, may focus on the distribution of racial groups across schools within districts, gauging the evenness with which a group is distributed across campuses (or entropy, per Reardon and Owens 2014). This barometer remained stable or improved slightly from 1993 to 2015 for Black and Latino students in the nation's school districts, not limited to metropolitan areas or elementary-age children (Richards, Stroub, and Kennedy 2020).…”
Section: Tr Acking Face Ts Of School Segreg At Ionmentioning
confidence: 99%